Assessment of knowledge, attitude and practice towards COVID-19 infection among residents of an urban slum in a metropolitan city - Bose, Aritra Kumar; Kasbe, Abhiram; Bandi, Janardan; Suryawanshi, Sudam R. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 is an infectious disease caused by a newly discovered coronavirus named SARS COV 2. By 26th August 2021, India added a record 37,593 cases of coronavirus infection, pushing the country’s COVID-19 tally to 32.5 million, while the death toll climbed to 4.35 million. This was declared as the second wave. The ICMR has calculated that compared to rural areas, the risk of spread was 1.09 times higher in urban areas and 1.89 times higher in urban slums. With all its elms, the urban slum can be a testing ground for appropriate awareness about the cause, prevention of COVID-19. Methods: The study was conducted in the field practice area of the Urban Health Centre of T. N. Medical College and B. Y. L. Nair Hospital situated in Mumbai. Approval for the conduction of the study was obtained from the Institutional Ethics Committee. The study was conducted over 1 month; i.e. from March 2021 to April 2021. The subjects were interviewed using a pre-designed interview schedule, information regarding education, occupation, marital status, and various information about knowledge, attitude and practice to prevent and protect against COVID-19 were obtained. Results: Majority of the study subjects were aged less than 50 years, with mean age of 44.92±16.16 years. With female predominance (56.0%), majority of subjects were literate (72.5%) with 55% of subjects educated till class 10 and 53.5% were employed. Seventy-seven percent subjects had elderly family members residing with them. Non-communicable diseases was observed in 75.5% subjects. Conclusions: The study highlighted the importance of effective and tailored health education programs aimed at improving COVID-19 knowledge, thereby leading to more favourable attitudes and implementation and maintenance of safe practices.